The impact of new media on reducing sports violence among Algerian football fans A field study - slimane.neme; bouzid.ouchene (sports creativity, 2025)
The aim of this study is to learn about the impact of the new media on reducing sports violence among the football audience, as well as to highlight the importance of the new media with its reliable technological dimensions in improving social relations. In order to achieve the objectives of this study, we used the descriptive approach. The sample size of the study consisted of 00 sports media from the different media. We also took 120 members from the sports audience. We used the questionnaire as a tool for study directed to the sports media on the one hand and the sports audience from the other. Our study of percentages and test (K 2). One of the main findings of our study is that the increase in sports violence is clearly related to the spread of new media and the increase in social networking sites.